Association between vitamin D level and pediatric inflammatory bowel disease: A systematic review and meta-analysis - Sun, Yan-hong; Tian, Dan-dan; Zhou, Jian-ming; Ye, Qing (Frontiers in Pediatrics, 2023)
Background: Previous studies have reported that the incidence of pediatric inflammatory bowel disease (IBD) is related to vitamin D, but it is still unclear. This study intends to calculate the relationship between pediatric IBD and vitamin D. Methods: A comprehensive literature search from inception to January 2023 was performed in the PubMed, EMBASE, Medline, Web of Science, and Google Scholar databases. Relevant data were extracted as required and used for subsequent calculations. Results: Sixteen papers were included, and there was no significant difference between the average vitamin D level in IBD patients and healthy controls. In addition, the overall pooled results showed that C-reactive protein (CRP) was 2.65 higher before vitamin D supplementation than after supplementation (SMD = 2.65, 95% CI = [2.26, 3.04]). Moreover, patients with IBD in remission were 0.72 higher before vitamin D supplementation than after supplementation (OR = 0.72, 95% CI = [0.52, 1.00]). Conclusion: This study suggested that there was no obvious relationship between pediatric IBD and vitamin D, while vitamin D supplementation can improve disease activity. Therefore, follow-up still needs many prospective studies to confirm the relationship between pediatric IBD and vitamin D.